2020
DOI: 10.1038/s41390-020-01249-w
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal corticosteroids: a reappraisal of the drug formulation and dose

Abstract: We review the history of antenatal corticosteroid therapy (ACS) and present recent experimental data to demonstrate that this, one of the pillars of perinatal care, has been inadequately evaluated to minimize fetal exposure to these powerful medications. There have been concerns since 1972 that fetal exposures to ACS convey risk. However, this developmental modulator, with its multiple widespread biologic effects, has not been evaluated for drug choice, dose, or duration of treatment, despite over 30 randomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 46 publications
0
40
0
4
Order By: Relevance
“…In animal studies, it was observed that, the loss of nitric oxide synthase (NOS) in the intestinal smooth muscle via combined inhibition of the neuronal NOS by steroids and endothelial NOS by indomethacin leads to disturbed intestinal motility and increases vulnerability of the intestine to perforation. [30][31][32] Extensive work on the pharmacokinetics and pharmacodynamics of antenatal steroids containing betamethasone 33 identified that the betamethasone acetate component of the combination, widely used in developed countries, is released very slowly in circulation, especially when given intramuscularly, leading to prolonged maternal and fetal levels for at least 4-6 days. This may explain coexposure having a pronounced effect when exposure to antenatal steroid was recent.…”
Section: Table I Maternal and Infant Baseline Characteristicsmentioning
confidence: 99%
“…In animal studies, it was observed that, the loss of nitric oxide synthase (NOS) in the intestinal smooth muscle via combined inhibition of the neuronal NOS by steroids and endothelial NOS by indomethacin leads to disturbed intestinal motility and increases vulnerability of the intestine to perforation. [30][31][32] Extensive work on the pharmacokinetics and pharmacodynamics of antenatal steroids containing betamethasone 33 identified that the betamethasone acetate component of the combination, widely used in developed countries, is released very slowly in circulation, especially when given intramuscularly, leading to prolonged maternal and fetal levels for at least 4-6 days. This may explain coexposure having a pronounced effect when exposure to antenatal steroid was recent.…”
Section: Table I Maternal and Infant Baseline Characteristicsmentioning
confidence: 99%
“…In animal models, betamethasone levels that are effective for lung maturation (1–4 ng/mL) have been detected in the umbilical cord at the time of prenatal administration. [ 20 ] Based on these models, it was determined that in pregnant women > 28 weeks, the intramuscular administration of 11.4 mg of betamethasone produces levels > 1 ng/mL in the umbilical cord from the first hour of administration and are maintained for up to 1.4 days. Levels below 1 ng/mL increase the risk of surfactant therapy [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggest that the long-acting betamethasone acetate is not ideal for an antenatal corticosteroid since it is associated with prolonged fetal exposure, carrying the risk of unwanted complications and side effects. 25 The dual acting formulation is designed to enhance its efficacy with the administration of single injection per day. This rationale is still questionable regarding its efficacy and safety.…”
Section: Discussionmentioning
confidence: 99%